Case series of intradural disc in recurrence of lumbar disc prolapse. Issue 2 (27th February 2021) - Alhani, Bashar; Nagappa, Satish; Baird, Charles; Botchu, Rajesh; Hughes, Simon; Mehta, Jewalant; Hassan, Faizul
Abstract: Intradural disc herniation is a rare entity reported at 0.04–1.1% that occurs most commonly in the lumbar spine particularly at L4–L5 region. There is a paucity of literature due to the rarity of this condition. Intradural disc herniations must be considered in the differential diagnosis of prolapsed intervertebral disc disease especially with recent worsening of symptoms and mismatch of unenhanced magnetic resonance induction (MRI) findings. The confirmation is made with intraoperative findings. An intradural disc herniation is most often diagnosed intraoperatively. Contrast enhanced MRI scan is mandatory for pre-operative diagnosis. We report on two cases presenting to our unit in the form of recurrent intradural disc disease following previous lumbar surgery occurring within 3 months of the index procedure in both cases.